Performing selves: The trope of authenticity and Robert Wilson's stage production of I La Galigo. (14th September 2015) - Davies, Sharyn Graham
Abstract : In 2010, La Galigo, a Bugis mythological epic describing the founding of the human world, was included in UNESCO's Memory of the World register. This accolade again brought La Galigo into the international spotlight, as had occurred when Robert Wilson's stage play I La Galigo, based on this epic, debuted in Singapore in 2004. Wilson's production received acclaim and critique, with reviews primarily focusing on his ability to achieve an authentic representation of Bugis identity and their past. These responses raise questions around the presupposition that there is an authentic Bugis identity and past that can be publicly recreated. This article analyses the concept of authenticity through reviews of Wilson's production and the work of key theorists to show that for many people, authenticity is achievable and of critical importance in underpinning any sense of a unified and singular ethnic identity, while for others, identity is always already a mix of different global influences and as such is either irrelevant, or liberated from a sense of a singular heritage.